A Novel Microsurgical Suturing Pilot Course for Ophthalmology Residents Based on Kern's Model for Curriculum Development - Roginiel, Aliya C.; Teng, Christopher C.; Chow, Jessica H. (Journal of Academic Ophthalmology, 2020)
Background Sutureless ophthalmic procedures are becoming more commonplace, reducing opportunities for ophthalmology residents to learn microsurgical suturing techniques. There is no standard curriculum in place to address this gap in clinical training among ophthalmology residency programs.Objective The aim of this study was to design, implement, and evaluate a preliminary microsurgical suturing curriculum for ophthalmology residents using Kern's six-step approach for curriculum development as a guideline, and the principles of distributed practice and guided, self-directed practice.Methods We designed a faculty-led teaching session on fundamental microsurgical suturing techniques for all 15 ophthalmology residents from Yale University over one academic year. Suturing skills were evaluated, followed by a guided teaching session, 30 days of self-directed practice time, and a re-evaluation of skills. The residents were evaluated through a written knowledge assessment and practical skills assessment. The residents also evaluated their skill level before and after the teaching session and practice period through written Likert-scale surveys. Data were evaluated in Excel using descriptive statistics and the paired t-test.Results After the session, postgraduate year 2 (PGY-2) residents felt more confident in recognition and use of surgical instruments (p < 0.01). PGY-3 residents felt less confident in their knowledge of microsurgical suturing after the session (p = 0.02). PGY-4 residents felt they were better able to identify different suture types after the session (p = 0.02). All residents improved on the written knowledge assessment (p < 0.001) and in all categories of the practical skills assessment (p < 0.001).Conclusions Implementation of a faculty-led microsurgical suturing training session, followed by 1-month of practice time, significantly improved residents' knowledge and practical application of various microsurgical suturing techniques that are necessary for performing common ophthalmic procedures.
Keywords: microsurgical suturing; microsurgical training; surgical skills assessment; resident training; Kern's model; distributed practice